2008
DOI: 10.1093/europace/eum272
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cardiac autonomic neuropathy in risk stratification of Brugada syndrome

Abstract: Aims Risk stratification in Brugada syndrome (BS) is controversial especially in asymptomatic individuals. The aim of this study was to evaluate the significance of cardiac autonomic neuropathy (CAN) in BS. Methods and results Patients diagnosed with Brugada ECG pattern were enrolled in the study. Four standard cardiac autonomic function tests were performed. The presence of 2 abnormal test results were considered definite evidence for the presence of CAN. Types 1, 2, and 3 Brugada ECG pattern were found in 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…Recently, Babaee and co‐workers could show a reduction of sympathetic function assesses by the sustained hand grip test in patients with BrS 6 . This nicely fits to our previous studies, in which we noted (1) an impaired adrenergic innervation using [ 123 I] metaiodobenzylguanidine single‐photon emission computed tomography ([ 123 I]MIBG‐SPECT) 7 and (2) an increased myocardial presynaptic catecholamine recycling 8 .…”
Section: Introductionsupporting
confidence: 90%
“…Recently, Babaee and co‐workers could show a reduction of sympathetic function assesses by the sustained hand grip test in patients with BrS 6 . This nicely fits to our previous studies, in which we noted (1) an impaired adrenergic innervation using [ 123 I] metaiodobenzylguanidine single‐photon emission computed tomography ([ 123 I]MIBG‐SPECT) 7 and (2) an increased myocardial presynaptic catecholamine recycling 8 .…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, autonomic instability during REM sleep and after arousals could play an important role in triggering arrhythmias. This may be especially true in Brugada patients, in whom an intrinsic autonomic impairment has been described 3032 . Studies using 123 I-MIBG-SPECT have shown reduced tracer uptake in the left ventricle of patients with the Brugada syndrome, which is compatible with a dysfunction in myocardial sympathetic innervation.…”
Section: Discussionmentioning
confidence: 94%
“…Studies using 123 I-MIBG-SPECT have shown reduced tracer uptake in the left ventricle of patients with the Brugada syndrome, which is compatible with a dysfunction in myocardial sympathetic innervation. Those patients may also have cardiac autonomic neuropathy, based on abnormalities evident in tests of cardiovascular sympathetic function 30 . Accordingly, the dynamic changes in the ST segment were more frequent during REM sleep and after arousals.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Furthermore, as important risk indicator of SUNDS, cardiac autonomic neuropathy was more common in males. 25 Thus, SUNDS was more prone to be males; especially manual workers often have high levels of fatigue. In addition, some victims suffered from stresses like bad mood before death.…”
Section: Discussionmentioning
confidence: 99%